Qualitative work overload and other risk factors related to hypertension risk among Indonesian Police Mobile Brigade (Brimob) (Medical Journal of Indonesia, 2008)
Members of the Police Mobile Brigade (Brimob) can suffer from hypertension which is related to work stressors and other risk factors. This study aimed to identify the relationship between work stressors and other hypertensive risk factors. The subjects of this cross-sectional study were members of the Brimob undergoing their periodic medical check-up during July-October 2007. A subject was hypertensive if systolic blood pressure (SBP) was 140 mmHg or higher, or diastolic (DBD) 90 mmHg, or higher or taking antihypertensive drugs. Normal subjects were those who had SBP less than 120 mmHg and DBP less than 80 mmHg, and have never been diagnosed with hypertension. A number of 336 Brimobs aged 21 to 51 years participated in this study, 111 had high blood pressure and 79 had normal blood pressure. Hypertension was found to be related to excessive body weight and qualitative work overload. Age, work, lifestyle, history of diabetes, hypertension in the family, and other work stressors were not found to increase the risk of hypertension. Medium to high level qualitative work overload had a two-fold risk for hypertension [relative risk adjusted (RRa) = 2.00; 95% confidence interval (CI) = 0.97-4.14; p = 0.060]. Overweight subjects had 48% increased risk to hypertension (RRa = 1.48; 95% CI = 0.98-2.22). Obese subjects had a two-fold risk of being hypertensive (RRa = 2.21; 95%CI = 1.51 - 3.14). Qualitative work overload and obesity increased the risk of hypertension. These risk factors should therefore be controlled. (Med J Indones 2008; 17: 188-96)